2017
DOI: 10.1038/s41598-017-05360-7
|View full text |Cite
|
Sign up to set email alerts
|

Two Bombyx mori acetylcholinesterase genes influence motor control and development in different ways

Abstract: Among its other biological roles, acetylcholinesterase (AChE, EC 3.1.1.7), encoded by two ace in most insects, catalyses the breakdown of acetylcholine, thereby terminating synaptic transmission. ace1 encodes the synaptic enzyme and ace2 has other essential actions in many insect species, such as Chilo suppressalis and Plutella xylostella. The silkworm, Bombyx mori, has been domesticated for more than two thousand years and its aces have no history of pesticide exposure. Here, we investigated the functional di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…It could also be that ChE vaccination affected the fecundity and egg maturity given the significantly smaller size of worms recovered from vaccinated groups, compared to controls. Indeed, previous studies on insects demonstrated that the suppression of AChE expression considerably reduced the weight and length of surviving organisms [39][40][41] and severely affected the hatching ability of the eggs laid [39,42]. These reports have suggested that dysregulated cell proliferation and apoptosis during larval growth may be reasons for such phenotypic effects attributed to the absence of AChE, although such a link in trematodes remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be that ChE vaccination affected the fecundity and egg maturity given the significantly smaller size of worms recovered from vaccinated groups, compared to controls. Indeed, previous studies on insects demonstrated that the suppression of AChE expression considerably reduced the weight and length of surviving organisms [39][40][41] and severely affected the hatching ability of the eggs laid [39,42]. These reports have suggested that dysregulated cell proliferation and apoptosis during larval growth may be reasons for such phenotypic effects attributed to the absence of AChE, although such a link in trematodes remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be that ChE vaccination affected fecundity and egg maturity given the significantly smaller size of worms recovered from vaccinated groups, compared to controls. Indeed, previous studies on insects demonstrated that suppression of AChE expression considerably reduced the weight and length of surviving organisms [35][36][37] and severely affected the hatching ability of the eggs laid [35,38]. These reports have suggested that dysregulated cell proliferation and apoptosis during larval growth may be reasons for such phenotypic effects attributed to the absence of AChE, although such a link in trematodes remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…The larvae were sorted according to their growth stages and maintained on fresh maize stem for approximately 3 days to adapt to the new artificial environment (26 °C ± 2 and 65% humidity). dsRNA were targeted against vital genes that have been reported to induce silencing in order Lepidoptera: Chitinase , Vacuolar ATPase , Arginine kinase 47 , acetylcholinesterase 45 , and cytochrome P450 48 . dsRNAs were induced in bacteria as described by 14 and purified according to 49 .…”
Section: Methodsmentioning
confidence: 99%